A Case of bacterial orbital cellulitis with complete ophthalmoplegia - Hemanth Ghanta; Suresh Harsoor (Wolters Kluwer Medknow Publications, 2020)
Orbital cellulitis (OC) refers to acute infection of soft tissues of the orbit behind orbital septum. As many as 11% cases of OC result in visual loss. Here, we report a 60-year-old female who is a known case of Type 2 diabetes mellitus presented with complaints of right-sided headache, unable to open right eyelid, and unable to move eyeball for 1 month. Magnetic resonance imaging brain with orbit contrast done showed right-sided OC with forming abscess. Nasal endoscopy was done and nasal swab culture showed growth of Staphylococcus aureus. The patient was kept on antibiotics and was discharged after improvement. Prompt diagnosis and proper management are essential for curing the patient with OC. This is particularly important to prevent visual loss and other severe life-threatening complications.